Faktor Permasalahan Interoperabilitas Pada Penerapan Building Information Modeling (BIM) Dalam Proses Analisis Dan Desain Struktur - Fitrah, Ridho Aidil; Amrina, Elita; Masrilayanti, Masrilayanti; Kurniawan, Ruddy; Sunaryati, Jati; Rizaldi, Phandu; Azizah, Hanifa Roja (Universitas Andalas, 2024)
Interoperability in the context of Building Information Modeling (BIM) refers to the ability of different systems, software, and platforms to collaborate and share BIM information effectively. This enables professionals in the construction industry to work together more efficiently and minimize the risk of data loss or communication errors. Effective BIM interoperability is a critical aspect of the success of BIM implementation in construction projects, from the design process to on-site construction. One phase in BIM is the analysis and design of structures. This research addresses the challenges that arise in implementing BIM interoperability between architectural models and analytical models in multi-story buildings. The study was conducted by simulating reinforced concrete and steel multi-story building models, and obtaining structural element designs using ETABS and Revit software in standardized formats. The simulation results are presented in a workflow that identifies the dominant factors in the interoperability issues of each software. The availability of add-ons or plugins between software is a key factor leading to inconsistencies in data and coordinates, as well as discrepancies in the design results from the analytical model to the architectural model in the process of creating shop drawings.